User Satisfaction on Mobile Apps: An Analytical Study on Omani Business Environment - Alkhafaji, Salah Mahdi (Archives of Business Research, 2016)
Currently numerous mobile apps are available to promote the business activities to the consumers. These mobile apps are developed to reach the customers easily through advanced provisions and technology. This study was conducted to measure the user’s satisfaction on those mobile apps in Omani business environment. Irrespective of business activities, mobile apps shall be developed and used in daily business activities. The study revealed that the respondents were highly satisfied with the mobile apps as they provide sufficient timely information about various business activities to the customers. The organizations should motivate the customers to use the mobile apps by removing the business boundaries.